Qualification of Alternative Jet Fuels - Rumizen, Mark A. (Frontiers in Energy Research, 2021)
Historically, the commercial aviation industry has relied on a very limited number of well-proven, conventional fuels for certification and operation of aircraft and engines. The vast majority of today’s engines and aircraft were designed and certified to operate on one of two basic fuels; kerosene-based fuel for turbine powered aircraft and leaded AVGAS for spark ignition reciprocating engine powered aircraft. These fuels are produced and handled as bulk commodities with multiple producers sending fuel through the distribution system to airports and aircraft. They are defined and controlled by industry consensus-based fuel specifications that, along with the oversight of the ASTM International aviation fuel industry committee, accommodate the need to move the fuel as a commodity. It was therefore expedient to build upon this framework when introducing drop-in jet fuel produced from non-petroleum feed stocks into the supply chain. The process developed by the aviation fuel community utilizes the ASTM International Aviation Fuel Subcommittee (Subcommittee J) to coordinate the evaluation of data and the establishment of specification criteria for new non-petroleum (alternative) drop-in jet fuels. Subcommittee J has issued two standards to facilitate this process; ASTM D4054 – “Standard Practice for Qualification and Approval of New Aviation Turbine Fuels and Fuel Additives”, and ASTM D7566 – “Standard Specification for Aviation Turbine Fuel Containing Synthesized Hydrocarbons”. This paper will describe how the aviation fuel community utilizes the ASTM International consensus-based process to evaluate new candidate non-petroleum jet fuels to determine if these new fuels are essentially identical to petroleum derived jet fuel, and, if they are, to issue specifications to control the quality and performance of these fuels.